Bacillus velezensis QSE-21 cell-free supernatant primes resistance and outperforms live cells in controlling Botrytis cinerea on tomato - Gao, Saisai; Han, Hongjia; Yang, Fan; Liu, Xinyang; Liang, Wenxing; Liu, Mengjie (Frontiers in Microbiology, 2025)
IntroductionBiological control agents (BCAs) offer an environmentally friendly alternative to chemical pesticides for plant disease management. However, the efficacy of live microbial BCAs is often compromised by ecological constraints. Cell-free supernatants (CFSs), derived from BCA fermentation, contain most active biocontrol compounds responsible for disease suppression and can be directly applied without introducing living organisms into the environment. Our prior work demonstrated that CFS from Bacillus velezensis QSE-21 (CFS-Q) directly inhibits the growth and development of Botrytis cinerea. This study investigates CFS-Q-induced systemic resistance in tomato plants and fruits against B. cinerea.MethodsTomato seedlings were foliar-sprayed with CFS-Q or controls. Systemic resistance was assessed by challenging distal leaves with B. cinerea. Comparative transcriptomics analyzed gene expression (RNA sequencing) in treated vs. untreated plants, with/without pathogen inoculation. Tomato fruits were sprayed with CFS-Q, live QSE-21 cells (Cell-Q), or LB medium (control group), followed by B. cinerea inoculation.ResultsApplication of CFS-Q triggered immune responses in tomato seedlings, conferring enhanced local and systemic resistance against B. cinerea without direct pathogen contact. Comparative transcriptomics revealed that CFS-Q treatment activated multiple immune signaling pathways in tomato, regardless of B. cinerea inoculation. This immune priming effect translated into significantly faster and stronger defensive reactions against B. cinerea attack. Crucially, compared to spraying live QSE-21 cells, spraying CFS-Q exhibited superior efficacy in controlling B. cinerea on tomato fruits.DiscussionCFS-Q operates via a dual mechanism: direct antagonism (established previously) and induced systemic resistance (ISR), evidenced by immune pathway activation. The priming effect ensures rapid defense mobil.